2010
DOI: 10.1099/mic.0.037291-0
|View full text |Cite
|
Sign up to set email alerts
|

The endolysins of bacteriophages CMP1 and CN77 are specific for the lysis of Clavibacter michiganensis strains

Abstract: Putative endolysin genes of bacteriophages CMP1 and CN77, which infect Clavibacter michiganensis subsp. michiganensis and C. michiganensis subsp. nebraskensis, respectively, were cloned and expressed in Escherichia coli. The His-tagged endolysin of CMP1 consists of 306 amino acids and has a calculated molecular mass of 34.8 kDa, while the His-tagged endolysin of CN77 has 290 amino acids with a molecular mass of 31.9 kDa. The proteins were purified and their bacteriolytic activity was demonstrated. The bacterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Genomes of members of the fifth group, mainly Vibrio phages, even do not reveal any sign of lysis cluster at all which makes them interesting candidates for examining their lysis mechanism and potentially identifying new muralytic enzymes. Since all bacteriophages of the N4-family known so far have gram-negative hosts, it was no surprise that nearly all of them encode genes for rather unspecific muramidases and no specific endopeptidases as often found in phages with gram-positive hosts [56]. Although the genomes of N4-like phages are highly conserved both in sequence identity and structure, it is interesting to observe these differences in their lysis clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Genomes of members of the fifth group, mainly Vibrio phages, even do not reveal any sign of lysis cluster at all which makes them interesting candidates for examining their lysis mechanism and potentially identifying new muralytic enzymes. Since all bacteriophages of the N4-family known so far have gram-negative hosts, it was no surprise that nearly all of them encode genes for rather unspecific muramidases and no specific endopeptidases as often found in phages with gram-positive hosts [56]. Although the genomes of N4-like phages are highly conserved both in sequence identity and structure, it is interesting to observe these differences in their lysis clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Coding sequences entirely encompassed within other genes seem to be very rare among dsDNA bacteriophages: λ rz and rz1 represent an example of two genes located in different reading frames in the same nucleotide sequence which encode different proteins, both required in the same physiological pathway [44]. Although very rare, some exceptions among bacteriophage endolysins were found: 1) the bacteriophage φvML3 endolysin gene encodes two proteins, a larger lysin that has homology with lysozymes and a smaller lysis protein that has some features resembling those of a holin [45]; 2) the streptococcal C1 bacteriophage lysin called PlyC is a multimeric lysin composed of two separate gene products, PlyCA and PlyCB responsible for the hydrolytic amidase activity and cell-wall-binding domain, respectively [46]; 3) examination of the nucleotide sequence of bacteriophage CMP1 endolysin gene revealed a possible Shine-Dalgarno sequence within the gene, four nucleotides upstream of a second ATG codon in the same reading frame which would correspond to a gene product consisting of 166 C-terminal amino acid residues that includes the binding domain of the enzyme [47].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with other Paenibacillus phages showed that they indeed also harbor either a gene for N-acetylmuramoyl L-alanine amidase, e.g., phage Emery, or a gene for an endo-beta-N-acetylglucosamidase, e.g., phage Davies (33). In particular, endolysins of phages with Gram-positive hosts often act as endopeptidases or amidases and exhibit highly specific activity (39). Therefore, endolysins from Paenibacillus phages could be a further option for the treatment of beehives.…”
Section: Discussionmentioning
confidence: 99%